Strategi Komunikasi Youtuber Penyandang Tuli Amanda Farliany dalam Mensosialisasikan Bahasa Isyarat Indonesia (BISINDO) - Rajagukguk, Sonya Theresia; Amanda Gelgel, Ni Made Ras; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2021)
This research is entitled “Amanda Farliany's Deaf Youtuber Communication Strategy in Socializing Indonesian Sign Language (BISINDO)”. This study uses a qualitative descriptive method with Harold D. Lasswell's Communication Strategy Theory. The purpose of this research is to find out how communication strategies conducted by deaf youtuber Amanda Farliany in socializing BISINDO on youtube media.The results showed that the communication strategy according to Lasswell's theory on Amanda Farliany's youtube is Amanda Farliany as the main communicator and her husband and children as supporting communicators. The message conveyed is in the form of an educational video with several concepts by providing translated text. Supporting media used are Facebook and Instagram. The communicants on Amanda Farliany's youtube are all people. The effect obtained is positive feedback from the audience.   Keywords : Communication Strategy, BISINDO, Youtube